Sugar Sweetened Beverage Consumption among Primary School Students: Influence of the Schools' Vicinity. (26th September 2016) - Lebel, Alexandre; Morin, Pascale; Robitaille, Éric; Lalonde, Benoit; Florina Fratu, Ramona; Bisset, Sherri
Abstract : The purpose of the research was to explore the associations between the characteristics of schools' vicinity and the risk of sugar sweetened beverage (SSB) consumption in elementary students. Findings exposed an important variation in student's SSB consumption between schools. Schools with a lower socioeconomic status or in a densely built environment tend to have higher proportion of regular SSB drinkers. These characteristics of the school's vicinity partly explained the variation observed between them. We estimated that a student moving to a school with a higher proportion of SSB drinkers may increase his/her chances by 52% of becoming a daily consumer. Important changes in dietary preferences can occur when children are in contact with a new social environment. Findings also support the idea that dietary behaviors among children result from the complex interactions between biological, social, and environmental factors.